Simplified evaluation of CGGTTS generation without navigation RINEX corrections: impact on UTC (INXE) - De Cicco, M. (2025)
The contribution to UTC by time and frequency laboratories is commonly achieved through RINEX and CGGTTS files derived from GNSS measurement data [1]. These text-based files are typically generated from continuous binary streams, from which partial extracts can be obtained. CGGTTS files conforming to the BIPM standard are produced by dedicated software using two preceding days of RINEX streams, where the navigation RINEX file provides critical ephemeris corrections, including precise orbital position coordinates for GNSS constellation satellites.